Antibody-mediated rejection. Issue 5 (October 2015) - Amore, Alessandro
Abstract : Purpose of review: Over the last five decades, the attention of nephrologists has focused on cellular rejection which was considered to be responsible for the early loss of function of the transplanted kidney. The use of new drugs in different combinations with steroids resulted in an improved short-term survival of the graft, which has significantly reduced the incidence of acute rejections. The main problem now, however, is ensuring the long-term survival of the transplanted kidney. This has become the challenge of the new millennium. Recent findings: The current literature clearly focuses on donor-specific alloantibodies, directed against human leukocyte antigen (HLA) and non-HLA antigens [donor-specific antibodies (DSA)], which have been shown to play an important role in graft dysfunction, longevity, and loss. To mitigate allograft loss due to antibodies, it is important to treat the source of antibody production, the plasma cells. Drugs used prior to 2007, such as Rituximab, intravenous immunoglobulins, and plasmapheresis, lack effects on these long-lived plasma cells. Their ability to remove DSA is incomplete and/or cost prohibitive. Since 2007, Bortezomib, a proteasome inhibitor, has been used to deplete plasma cells, thus eliminating the synthesis of DSA. Summary: Antibody-mediated rejection (AMR) is common in patients with DSA and is associated with a poor prognosis. Novel medications that target each step of AMR pathogenesis have been produced and are successful when compared with more traditional therapies.